2006
DOI: 10.1068/p5443
|View full text |Cite
|
Sign up to set email alerts
|

Visual Transients Reveal the Veridical Position of a Moving Object

Abstract: Article (Published Version) http://sro.sussex.ac.uk Kanai, Ryota and Verstraten, Frans A J (2006) Visual transients reveal the veridical position of a moving object. Perception, 35 (4). pp. [453][454][455][456][457][458][459][460] This version is available from Sussex Research Online: http://sro.sussex.ac.uk/43994/ This document is made available in accordance with publisher policies and may differ from the published version or from the version of record. If you wish to cite this item you are advised to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…A recent study using face stimuli (Khurana, Carter, Watanabe, & Nijhawan, 2006) obtained results consistent with ours, although their findings could be explained by possibilities other than knowledge, such as a priming effect and a similarity of visual features between the two halves of their nonchimera faces. Taken together with several studies indicating an involvement of high-level neural mechanisms in the FLE (Kanai & Verstraten, 2006;Nieman, Nijhawan, Khurana, & Shimojo, 2006), our study strengthens the view that at least some portions of the flash-lag illusion cannot be attributed to low-level processing in the visual system.…”
Section: Implications and Mechanisms Of The Knowledge-based Correctiosupporting
confidence: 88%
“…A recent study using face stimuli (Khurana, Carter, Watanabe, & Nijhawan, 2006) obtained results consistent with ours, although their findings could be explained by possibilities other than knowledge, such as a priming effect and a similarity of visual features between the two halves of their nonchimera faces. Taken together with several studies indicating an involvement of high-level neural mechanisms in the FLE (Kanai & Verstraten, 2006;Nieman, Nijhawan, Khurana, & Shimojo, 2006), our study strengthens the view that at least some portions of the flash-lag illusion cannot be attributed to low-level processing in the visual system.…”
Section: Implications and Mechanisms Of The Knowledge-based Correctiosupporting
confidence: 88%
“…The flash-lag illusion is a robust effect and, to our knowledge, only one study has found a lack of mislocalization between flashes and moving objects (Kanai & Verstraten, 2006). Kanai and Verstraten found that when a ring was flashed surrounding a moving disk, the percept corresponding to the disk split in two: one disc was perceived ahead of the flashed ring which reproduced the flash-lag effect, but the other appeared just centered inside the flashed ring showing no relative spatial mislocalization.…”
Section: Discussionmentioning
confidence: 92%
“…While the relatively slow buildup of these positional displacements might argue for some role of feedback (Chung et al, 2007), the physiological data described above do not provide any direct evidence for effects arising within primary visual cortex (McGraw et al, 2004; Whitney et al, 2003). Additionally, behavioral evidence suggests that visual transients can restore the veridical position of moving elements (Kanai & Verstraten, 2006). This suggests that the De Valois effect is a later-stage process in vision, with the veridical signals maintained within the initial processing stages.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of the De Valois effect using functional MRI have shown that its magnitude does not correlate with activity in V1 (Whitney et al, 2003) and that it is disrupted only by transcranial magnetic stimulation (TMS) over area MT/V5, with no discernable effects from TMS over V1 (McGraw, Walsh, & Barrett, 2004). Further, visual transients can restore the veridical position of moving elements, suggesting that these veridical signals are maintained within V1 throughout (Kanai & Verstraten, 2006). Positional shifts can nonetheless be induced by crowded motion signals (Whitney, 2005), suggesting that these effects are produced by mid-level mechanisms.…”
Section: Introductionmentioning
confidence: 99%